Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/jacs.2c03669
|View full text |Cite
|
Sign up to set email alerts
|

Urea-Bond Scission Induced by Therapeutic Ultrasound for Biofunctional Molecule Release

Abstract: Ultrasound-triggered remote control of biomolecular functions in cells provides unique advantages for us to interrogate nature. However, strategies to design therapeutic ultrasound-responsive functional molecules remain elusive, and rare ultrasound-cleavable chemical bonds have been developed to date. Herein, therapeutic ultrasound (1 MHz)-induced scission of urea bonds for drug release is demonstrated for the first time. Such a transformation has been verified to be initiated by hydroxyl radicals generated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 60 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…As we know, fluorescence imaging based on fluorescent probes is allowed to perform in vitro, ex vivo, and in vivo images and provide an analysis with higher sensitivity. [11][12][13][14][15][16][17][18][19] It has surfaced as a powerful tool for visualizing target analytes in complicated biological specimens owing to its real-time detection, non-destructive analysis and, especially, excellent sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…As we know, fluorescence imaging based on fluorescent probes is allowed to perform in vitro, ex vivo, and in vivo images and provide an analysis with higher sensitivity. [11][12][13][14][15][16][17][18][19] It has surfaced as a powerful tool for visualizing target analytes in complicated biological specimens owing to its real-time detection, non-destructive analysis and, especially, excellent sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In a recent report by Peng and co-workers, ultrasound-induced cavitation effectively generated OH radicals by sonolysis 13 to activate methylene blue-based urea conjugates for both imaging and therapeutic applications. 14 Inspired by this strategy, we rationalised the recently reported OH radical responsive unit, 3,5-dihydroxylbenzyl (DHB) 4 may afford a general ''sonocaging'' unit that is selectively removed by OH radicals generated from ultrasound irradiation. It is proposed OH radical-mediated aromatic hydroxylation results in self-immolation releasing the active molecule (Scheme 1).…”
mentioning
confidence: 99%
“…To overcome these limitations, Peng et al developed a US-activatable molecule, and the •OH produced by cavitation bubbles acted as an "intermediary" to trigger the urea bond cleavage for drug release (demonstrating excellent •OH responsiveness) under therapeutic US conditions (1 MHz). 11 This new way of bridging US chemistry with bond scission via an "intermediary" is novel and meaningful with wide application prospects.…”
mentioning
confidence: 99%
“…As a promising alternative, ultrasound (US) not only exhibits noninvasiveness and high spatiotemporal control similar to light but also has the advantages of deep penetrability (up to 10 cm), minimal side effects, precise localization of lesions, and low cost. Recent studies have shown that the US cavitation effect-driven mechanical force can act as an energy stimulus, triggering specific chemical reactions. , Herrmann’s group designed a disulfide-centered polymer carrying camptothecin anticancer drugs. The disulfide was transformed to thiols under US radiation, achieving efficient drug release and activation .…”
mentioning
confidence: 99%
See 1 more Smart Citation